Pengaruh Persepsi Kemudahan dan Persepsi Keamanan terhadap Keputusan Pengguna E-Wallet OVO : (Studi pada Mahasiswa Aktif Universitas Negeri Jakarta) - Chairunissa Rizkina Rosani; Dedi Purwana; Shandy Aditya (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This study aims to test the influence of Perceived Ease and Perceived Security on the Decision of OVO E-Wallet Users. The data collection method uses a survey with an instrument in the form of a questionnaire distributed online. The population used is Active Students of Jakarta State University (D3, D4, S1) with the criteria of Domiciled in Jabodetabek; aged 18 years and over; and have used the OVO E-wallet service as a payment transaction method in the last 2 weeks. This study involved 100 respondents, and the data was analyzed using SPSS Version 29 to manage data and analyze the results of the study using multiple linear regression equations. The results of the study indicate that 1) perceived ease has a positive and significant effect on user decisions, 2) perceived security has a positive and significant effect on user decisions, 3) perceived ease and perceived security simultaneously influence user decisions.